The Influence of Food Safety and Health Behaviour on Purchase Intention and Its Implications for Purchase Decisions at Oish Bakery - Muhammad Rendy Muliawan; Ambar Lukitaningsih; Nonik Kusmaningrum (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyse the effect of food safety and health behaviour on purchase intention and its implications for purchase decisions among Oish Bakery consumers. The research method used is a quantitative approach with a survey technique involving 120 respondents. Data analysis uses multiple linear regression analysis and mediation tests. The results of the study indicate that food safety and health behaviour have a positive effect on purchase intention. Purchase intention has been proven to have a significant effect on purchase decisions and mediates the effect of food safety and health behaviour on purchase decisions. These findings indicate that improving food safety and health is an important strategy in increasing consumer purchase intention and purchase decisions in the bakery industry.